Ureteral Stricture Outcomes Using Small Ureteral Access Sheath During Retrograde Intrarenal Surgery - Özer Güzel; Melih Balcı; Altuğ Tuncel; Ahmet Asfuroğlu; İbrahim Can Aykanat; Yılmaz Aslan (Journal of Urological Surgery, 2023)

(untitled)
Objective: This study evaluated ureteral injury and long-term stricture progression after the smallest ureteral access sheath (UAS) application during retrograde intrarenal surgery. Materials and Methods: A total of 154 patients who had undergone retrograde intrarenal surgery procedures and applied a 9.5/11.5-F UAS for kidney stones between September 2016 and March 2019 were prospectively included, and intraoperative, postoperative, and late complications were evaluated. Ureteral injuries were visualized using flexible and semi-rigid ureterorenoscopy, and ureteral stricture was assessed by computed tomographic urography at one-year controls. Results: 56% (n=86) of the patients were males, and %45 (n=68) the mean age was 47±15 years, stone size was 17.1±8 mm, operative time was 56±23 minutes, 80% had ureter wall injury, and 39% and 41% had grade 0 and grade 1 lesions, respectively. Minor complications were developed in 3%, and major complications were seen in 2% of cases. The ureteral stricture was not observed in 1st-year controls. Conclusion: The routine application of 9.5/11.5-F UAS is safe to use in flexible ureteroscopy without any long-term adverse effects.